The Effects of Malonic Acid Derivatives and Acetic Acid Derivatives as Coadsorbents on the Photovoltaic Performance of Dye-Sensitized Solar Cells. (27th June 2013) - Matsuyoshi, Hiroaki; Tomita, Haruo; Nishino, Hitoshi; Sakamoto, Hiroki; Manabe, Kyohei
Abstract : The effects of malonic acid derivatives and acetic acid derivatives as coadsorbents on the photovoltaic performance of D908 dye-sensitized nanocrystalline TiO2 solar cells were investigated. Each of phenylmalonic acid (PMA) and cyclopentylacetic acid (CPEAA) coadsorptions was revealed to improve both the photocurrent and the photovoltage of the solar cells. The improved photocurrent was probably due to the suppression of self-quenching of the excited electrons in the dyes by coadsorption of PMA or CPEAA on the TiO2 that increased in the electron-injection yields from the dye to the TiO2 . The improved photovoltage was probably due to suppression of recombination between the injected electrons and I 3 - ions on the TiO2 surface. ATR-FTIR spectroscopy indicated that PMA or CPEAA coadsorption increased the content of bound dye on the TiO2 surface. This result suggests that PMA or CPEAA coadsorption improved the photocurrent of the solar cells. Electrochemical impedance spectroscopy indicated that PMA or CPEAA coadsorption on the TiO2 surface increased the charge recombination resistance (R2) and decreased the diffusion resistance in the electrolyte (R3). These results suggest that the coadsorption of PMA or CPEAA on the TiO2 may improve its photovoltage and photocurrent.